Waterbird diversity and spatial distribution across China: Patterns and conservation strategies - Lu Yang; Ping-An Liu; Rong-Xing Wang (Global Ecology and Conservation, 2025)
Understanding regional patterns of waterbird distribution and community assembly is crucial for effective conservation in China. However, comprehensive nationwide analyses of waterbird spatial distribution remain limited. Elucidating these patterns and underlying mechanisms and developing corresponding conservation strategies is imperative. We compiled waterbird data from citizen science reports and publications (2000–2022) to investigate the spatial distribution and community assembly of the waterbirds across China, proposing region- and season-specific conservation recommendations. Our analysis of 243 recorded waterbird species revealed a distinct north–south distribution pattern centered on approximately 35° latitude. Southern regions predominantly hosted resident and wintering species, whereas northern regions were dominated by summer visitors and migrants. This pattern persisted for both total and threatened/protected species. Community composition varied substantially across lake zones, likely influenced by temperature and migratory status. Resident and wintering communities displayed high compositional similarity across most lake zones, except in the Northeast Plain and Mountain Lake Zone, whereas breeding and migratory communities exhibited a more pronounced east–west differentiation. The assembly of waterbird communities is scale-dependent and varies with migratory status, with environmental filtering and neutral processes dominating at the gamma and beta scales, respectively. The findings of this study highlight the need for spatially and temporally tailored national conservation strategies that prioritize habitat protection and mitigation of climate change and human impacts. Locally, efforts should focus on enhancing habitat connectivity via ecological corridors to support waterbird dispersal.